2015
DOI: 10.1093/icb/icv004
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Prey, Feeding, and Functional Anatomy of the Jaws in Velvet Worms (Onychophora)

Abstract: Onychophorans are carnivorous, terrestrial invertebrates that occur in tropical and temperate forests of the Southern Hemisphere and around the Equator. Together with tardigrades, onychophorans are regarded as one of the closest relatives of arthropods. One of the most peculiar features of onychophorans is their hunting and feeding behavior. These animals secrete a sticky slime, which is ejected via a pair of slime-papillae, to entangle the prey. After the prey has been immobilized, its cuticle is punctured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
0
26
0
4
Order By: Relevance
“…spiders, mussels) have emerged as important role models for inspiring sustainable production of advanced polymeric materials 14 . Velvet worms (Onychophora) are terrestrial invertebrates inhabiting humid microhabitats of tropical and temperate forests in the southern hemisphere 5 , which deploy a fibre-forming projectile slime for defence and entangling prey 68 . The adhesive slime, which is stored as a fluid within slime gland reservoirs, is ejected through papillae—small nozzles on either side of the head—leading to the rapid self-assembly into sticky entangling threads outside the body, which dry and harden into stiff polymeric fibres (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…spiders, mussels) have emerged as important role models for inspiring sustainable production of advanced polymeric materials 14 . Velvet worms (Onychophora) are terrestrial invertebrates inhabiting humid microhabitats of tropical and temperate forests in the southern hemisphere 5 , which deploy a fibre-forming projectile slime for defence and entangling prey 68 . The adhesive slime, which is stored as a fluid within slime gland reservoirs, is ejected through papillae—small nozzles on either side of the head—leading to the rapid self-assembly into sticky entangling threads outside the body, which dry and harden into stiff polymeric fibres (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Die Stummelfüßer bilden eine eigenständige, stammesgeschichtlich sehr alte Gruppe von weichhäutigen, wirbellosen Tieren, die hauptsächlich in den Wäldern der südlichen Hemisphäre unserer Erde vorkommen (Abbildung ). Dort leben sie in feuchten Lebensräumen, verborgen in verrotteten Baumstämmen oder in der Spreuschicht . Derzeit gibt es knapp über 200 beschriebene Arten, aber vor allem in Brasilien werden viele noch unbekannte Arten vermutet.…”
Section: Die Jagd‐ Und Abwehrstrategie Der Stummelfüßerunclassified
“…Sobald die Beute fixiert ist, reißt der Räuber die Körperhülle mit seinen kräftigen Kiefern auf und injiziert einen Cocktail aus Enzymen, welche das Innere der Beute verdauen. Der Stummelfüßer saugt dann die flüssige Nahrung aus, ähnlich wie es bei den Spinnen zu beobachten ist . Die großen Mengen an versprühtem Beutefangsekret sind für die Tiere sehr wertvoll.…”
Section: Die Jagd‐ Und Abwehrstrategie Der Stummelfüßerunclassified
See 1 more Smart Citation
“…In particular, onychophorans are pivotal for understanding intricate evolutionary processes underlying the successful radiation of arthropods, such as arthropodisation (evolution of jointed limbs), arthrodisation (evolution of body sclerotisation), tagmatisation (fusion of body segments into functional units) and establishment of a specialised ganglionated nervous system (Martin et al ., ). Even though onychophorans have never been investigated comprehensively by CT techniques, recent studies suggested that this method is promising for studying their anatomy and may eventually help to shed light on evolutionary questions that remain unanswered (Mayer et al ., ; Müller et al ., ).…”
Section: Introductionmentioning
confidence: 98%